2019
DOI: 10.1016/j.advwatres.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of hyporheic exchange and fine particle deposition in a riverbed

Abstract: Hyporheic flow transports fine particles into the riverbed, which can lead to clogging of the bed and in turn affect hyporheic flow and exchange processes. Field measurements and numerical simulations show the formation of a low-permeability layer (LPL) near the bed surface due to fine particle clogging, and consequently reduction of exchange fluxes between the bed and river water. A characteristic porosity (* * . The results also showed significant effects of the fine particle concentration, pressure differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 58 publications
(87 reference statements)
3
18
0
Order By: Relevance
“…The infiltration patterns in treatment flumes could be largely attributed to the transport of clay particles due to advective pumping and gravitational settling mechanisms. For all the treatment flumes, a preferential deposition of clay particles at the stoss‐side of the dunes indicates transport of fines along the downward advective hyporheic flow paths as also demonstrated in some previous investigations (C. Chen et al, 2010; G. Jin, Chen, et al, 2019). The fine sediment infiltration at the lee‐side of the dunes occurred potentially due to the settling of particles.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The infiltration patterns in treatment flumes could be largely attributed to the transport of clay particles due to advective pumping and gravitational settling mechanisms. For all the treatment flumes, a preferential deposition of clay particles at the stoss‐side of the dunes indicates transport of fines along the downward advective hyporheic flow paths as also demonstrated in some previous investigations (C. Chen et al, 2010; G. Jin, Chen, et al, 2019). The fine sediment infiltration at the lee‐side of the dunes occurred potentially due to the settling of particles.…”
Section: Discussionsupporting
confidence: 83%
“…The fine sediment infiltration at the lee‐side of the dunes occurred potentially due to the settling of particles. This argument is supported by results from a recent study (G. Jin, Chen, et al, 2019) which demonstrated that fine particles do not accumulate at the lee side of the dunes in the absence of settling phenomenon. The lee side of the dunes corresponds to the upwelling zones and the deposition of clay particles in these areas indicates that settling velocities of the particles dominated the upwelling hyporheic flow.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The model application to laminar flow is justified here by the predominance of low Strahler order rivers (<2) accounting for 75% of the global river length (Downing, 2012). The limited velocity in low Strahler order rivers favors laminar flow, except during floods, and sediment bed clogging even from coarse sand riverbed (Jin et al., 2019), which limits turbulent flow penetration into the sediment bed. The model is thus valid below the critical Reynolds number.…”
Section: The Frt Numerical Modelmentioning
confidence: 99%
“…During flow from surface water to the underlying sediments, a downward seepage force acts in concert with gravity to compress or transport fine‐grained sediments deeper into interstices, creating additional flow restrictions and reducing K v . This is common in fluvial settings where bedforms project into the flow field, even if there is no larger‐scale downward hydraulic gradient (e.g., Jin et al, 2019; Packman & MacKay, 2003). During upward flow, the force associated with upward seepage opposes the gravity force exerted on each sediment grain.…”
Section: Introductionmentioning
confidence: 99%